A Non‐Ionic Precursor for Preparing Di‐, Tetra‐, Hexanitro‐2, 4, 6, 8, 10, 12‐hexaazatricyclo[7, 3, 0, 03, 7]dodecane‐5, 11‐dione: Synthesis, Mechanism and Properties. Issue 45 (2nd December 2021) - Zhang, Xiya; Lin, Xiangyang; Huang, Haifeng
Abstract: A non‐ionic precursor 2, 4, 6, 8, 10, 12‐hexaazatricyclo[7, 3, 0, 0 3, 7 ]dodecane‐5, 11‐dione (HTDD ) was applied to synthesize hexanitro‐2, 4, 6, 8, 10, 12‐hexaazatricyclo[7, 3, 0, 0 3, 7 ]dodecane‐5, 11‐dione (HHTDD ) and its derivatives. The calculation of the electrostatic potential (ESP) shows that the non‐ionic precursor has a stronger electrophilic reactivity compared to the previous ionic analogue, which is also verified by nitrification experiments. 90 % HNO3 was reacted with the ionic precursor and the non‐ionic precursor, respectively, and only the latter can obtain a full nitrification product. All nitrification products with different nitro group numbers were characterized by FT‐IR, NMR, element analysis, DSC, TG and single‐crystal XRD. The hydrolytic stability was tested in different concentrations of acidic and alkaline solutions. The impact and friction sensitivities were measured. Further the detonation parameters were determined according to the Kamlet‐Jacobs equations based on calculated heats of formation (B3LYP) and measured densities. The results show that the non‐ionic precursor has a stronger electrophilic reactivity and is easier to react with NO2 + . Applying a non‐ionic precursor is a very efficient method for promoting nitrating reactions. Abstract : A non‐ionic precursor 2, 4, 6, 8, 10, 12‐hexaazatricyclo[7, 3, 0, 0 3, 7 ]dodecane‐5, 11‐dione (HTDD ) is designed and applied to synthesize 2, 4, 6, 8, 10, 12‐hexaazatricyclo[7, 3, 0, 0 3, 7 ]dodecane‐5, 11‐dione (HHTDD) and its derivatives. The non‐ionic precursor has stronger electrophilic reactivity and is easier to react with NO2 + compared to the ionic analogue, and the products can be obtained under moderate nitration condition.